2020
DOI: 10.1556/650.2020.31854
|View full text |Cite
|
Sign up to set email alerts
|

A réz élettani funkciója, a rézfelhalmozódás és a rézhiány kóroktani szerepe

Abstract: Absztrakt: A réz esszenciális nyomelem az emberi szervezet számára, fontos szerepet tölt be számos anyagcsere-folyamatban. Nélkülözhetetlen többek között a légzési lánc és a vasanyagcsere helyes működéséhez, a szabad gyökök eliminációjához, a hormonok, neurotranszmitterek szintéziséhez, valamint az extracelluláris mátrix stabilizálásához. A réz az oxidációs állapotváltozásra képes mivoltának kös… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Copper is an essential element, and it enters a lot of physiological functions, being a part of different enzymes and proteins. For example, copper is required for terminal oxidation and the elimination of free radicals and is involved in the synthesis of hormones and iron metabolism [ 36 ]. Both copper deficiency and poisoning, especially in ruminants, are responsible for nutritional and nutrition-related diseases and, in the case of livestock, for economic losses due to the mortality of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is an essential element, and it enters a lot of physiological functions, being a part of different enzymes and proteins. For example, copper is required for terminal oxidation and the elimination of free radicals and is involved in the synthesis of hormones and iron metabolism [ 36 ]. Both copper deficiency and poisoning, especially in ruminants, are responsible for nutritional and nutrition-related diseases and, in the case of livestock, for economic losses due to the mortality of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the dual role of metallic copper in tumor progression, this area is becoming a hot research topic in cancer biology. Copper is a valuable coenzyme in the metabolism of organisms (30), and the imbalance of copper ion homeostasis in the human body is also closely related to various diseases (31). Increasing evidence has shown that copper plays vital roles in tumor cell proliferation, angiogenesis, and cancer metastasis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Copper homeostasis is important in the proper functioning of various physical and biological processes. Copper homeostasis imbalance is closely correlated with various diseases 26 . Evidence from previous studies has demonstrated that copper is critical in tumor cell proliferation, angiogenesis, and metastasis 27 .…”
Section: Discussionmentioning
confidence: 99%